2005
DOI: 10.1021/jp053233r
|View full text |Cite
|
Sign up to set email alerts
|

Rate Constants and Kinetic Isotope Effects for Unimolecular 1,2-HX or DX (X = F or Cl) Elimination from Chemically Activated CF3CFClCH3-d0, -d1, -d2, and -d3

Abstract: Chemically activated CF(3)CFClCH(3), CF(3)CFClCD(3), CF(3)CFClCH(2)D, and CF(3)CFClCHD(2) molecules with 94 kcal mol(-1) of internal energy were formed by the combination of CF(3)CFCl radicals with CH(3), CD(3), CH(2)D, and CHD(2) radicals, which were generated from UV photolysis of CF(3)CFClI and CH(3)I, CD(3)I, CH(2)DI, or CHD(2)I. The total (HF + HCl) elimination rate constants for CF(3)CFClCH(3) and CF(3)CFClCD(3) were 5.3 x 10(6) and 1.7 x 10(6) s(-1) with product branching ratios of 8.7 +/- 0.6 in favor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(64 citation statements)
references
References 43 publications
(92 reference statements)
3
61
0
Order By: Relevance
“…Holmes et al. have calculated the threshold energies for HF and HCl elimination from HCFC‐244bb, which are 61.3 and 58.5 kcal mol −1 , respectively . This small energy difference suggests the selective control of above reaction is not easy.…”
Section: Introductionmentioning
confidence: 99%
“…Holmes et al. have calculated the threshold energies for HF and HCl elimination from HCFC‐244bb, which are 61.3 and 58.5 kcal mol −1 , respectively . This small energy difference suggests the selective control of above reaction is not easy.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we describe an apparently simple and fundamental organic reaction, hydrogen halide elimination (or dehydrohalogenation), where both concerted and sequential mechanisms of proton coupled electron transfer are operative. Dehydrohalogenation reactions of haloalkanes have been extensively studied [16], [17], [18], [19], [20], [21], [22], and the role of charge transfer has previously been implicated [20]. For example, in the series of monohaloethanes C2H5X (X = F, Cl, Br, I), it was shown that the barrier to HX elimination correlates more strongly with the heterolytic (C − X → C + + X: − ) than homolytic (C − X → C + X ) bond dissociation energy [21].…”
Section: Introductionmentioning
confidence: 99%
“…11 Our experience is that when the E 0 (interchange) ≤ 290 kJ/mol the interchange reaction will be competitive with other decomposition processes for our chemical activation method that forms reactants with 350-420 kJ/mol of internal energy. [1][2][3][4][5][7][8][9][10][11] Scanning Tables 1 and 2 suggests that the interchange of Cl or Br might be observed with all of the groups in Table 1 results confirm E 0 (Cl-CH 3 ) = 259 kJ/mol for the CH 3 -Cl interchange reaction for 2,2-dimethyl-1chloropropane; i.e., two methyl groups replace two hydrogen atoms on C-2 of 1-chloropropane. 20 In addition, reactions with E 0 (interchange) > 290 kJ/mol might be observed for photochemical and thermal activation methods that prepare reactants with energy greater than 400 kJ/mol.…”
Section: R a F Tmentioning
confidence: 80%
“…In previous studies we have demonstrated the existence of a series of unimolecular, gas-phase reactions involving the interchange of two halogen (F, Cl and Br) atoms on adjacent carbon atoms. [1][2][3][4][5] This interchange mechanism has been supported by experimental and computational evidence for CF 2 ClCF 2 CH 3 , 1, 2 CF 2 ClCF 2 CD 3 , 1, 2 CHF 2 CH 2 Cl, 6,7 13 and CF 2 ClCH 2 F 13 and can be competitive with unimolecular 1,2-HX (X = F, Cl, or Br) eliminations. These halogen-interchange processes are also known as type-1 dyotropic [14][15][16][17][18][19] rearrangement reactions and a number of computational studies have appeared for interchange of halogens.…”
Section: Introductionmentioning
confidence: 89%